1990
DOI: 10.1007/bf01771456
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of natural killer activity and natural killer cell subsets in patients with bladder cancer

Abstract: In order to analyze the state of the natural resistance system of bladder cancer patients in vivo, we measured natural killer (NK) activity and NK cell subsets of peripheral blood lymphocytes (PBL) from 46 patients with bladder cancer and 25 age- and sex-matched healthy volunteers. The mean NK activity in patients with low-stage bladder cancer was similar to that in the controls, while NK activity in patients with high-stage bladder cancer was significantly depressed. The mean proportions of Leu7+ cells in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
1
9
1
Order By: Relevance
“…They hypothesized that unfavorable prognosis related to the presence of TILs may be connected to the inhibitory mediators released by the tumor cells. These results are in contrast to the findings obtained by other authors, who reported good prognosis for the patients with higher number of TILs (23-25). …”
Section: Discussioncontrasting
confidence: 99%
“…They hypothesized that unfavorable prognosis related to the presence of TILs may be connected to the inhibitory mediators released by the tumor cells. These results are in contrast to the findings obtained by other authors, who reported good prognosis for the patients with higher number of TILs (23-25). …”
Section: Discussioncontrasting
confidence: 99%
“…Delayed onset may result from reduced exposure to carcinogenic factors in the diet or lifestyle changes or by using chemopreventive agents that inhibit carcinogen uptake, maintain tumor suppressor function, or modulate immune responses. Increased immune responses have been reported in patients with cancer (6)(7)(8)(9), and patients that relapse have significantly lower preoperative NK cytotoxicity than relapse-free patients (10). These observations indicate that NK cells are candidates for cells that destroy tumor cells and that they may function as the first line in host defense against tumorigenesis.…”
Section: Introductionmentioning
confidence: 91%
“…Several studies have demonstrated the presence of large amounts of tumour infiltrating lymphocytes (TILs) in both muscle-invasive and superficial bladder tumours. Most of these data have correlated higher numbers of TILs with a good prognosis and survival rate (Ikemoto et al, 1990;Lopez-Beltran et al, 1989;Morita et al, 1990;Tsujihashi et al, 1988) especially in patients with advanced stages of tumour development (Lipponen et al, 1992;Sharma et al, 2007). These TILs are functional and can kill their autologous tumour in vitro (Housseau et al, 1997).…”
Section: Introductionmentioning
confidence: 99%